2013
DOI: 10.1179/1607845413y.0000000113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative haematological parameters of HbAA and HbAS genotype children infected withPlasmodium falciparummalaria in Yemen

Abstract: Infection with Plasmodium falciparum malaria caused more significant haematological alterations of HbAA children than HbAS. This study supports the observation that sickle cell trait seems to be a beneficial genetic factor that resists malaria, since inheriting it protects against significant haematological consequences of malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 33 publications
6
19
1
2
Order By: Relevance
“…A comparison of these frequencies indicated that the percentage of SCA picked up by neonatal screening in children with severe anaemia ranged from 1% globally to 3% in Kinshasa. This may be due to the fact that haemoglobin-AS protected children from malaria and this, in turn, reduced the frequency of children with severe anaemia that had the sickle cell trait, as reported in previous studies (24,25).…”
Section: Discussionsupporting
confidence: 63%
“…A comparison of these frequencies indicated that the percentage of SCA picked up by neonatal screening in children with severe anaemia ranged from 1% globally to 3% in Kinshasa. This may be due to the fact that haemoglobin-AS protected children from malaria and this, in turn, reduced the frequency of children with severe anaemia that had the sickle cell trait, as reported in previous studies (24,25).…”
Section: Discussionsupporting
confidence: 63%
“…The results of this study revealed that 73% of the malaria positive participants had the haemoglobin genotype AA (HbAA), which was higher than the percentages in the other genotypes (HbAS [23%]) and HbAC [3%]). This is similar to the reports of Albiti and Nsiah [40] and Akanbi [39]. The prevalence of participants with HbAS and HbAC were quite low compared to HbAA.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, such alterations have also been common in malaria, and reported to be more pronounced in P. falciparum infection for the HbAA genotype (21,38). However, the magnitude of such alterations differ depending on genetic, and epigenetic factors (22). Our study provides a unique approach by not only looking at the comparisons of the haematological parameters in sickle cell genotypes in P. falciparum infection but also determines the association of these parameters to sickle cell gene in the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides a unique approach by not only looking at the comparisons of the haematological parameters in sickle cell genotypes in P. falciparum infection but also determines the association of these parameters to sickle cell gene in the infection. A few studies have been carried out in African countries where malaria is holoendemic with varied demonstrations on the protective effect of sickle cell gene (HbAS and HbSS) of asymptomatic and symptomatic P. falciparum infection of variable severity (14,20,22,23). None of the above studies have speci cally described haematological differences on the basis of sickle cell genotypes in children presenting with steady state of P. falciparum malaria apart from Prohit et al (24) and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation